Vascular pentraxin 3 controls arterial thrombosis by targeting collagen and fibrinogen induced platelets aggregation - Bonacina, F.; Barbieri, S.; Cutuli, L.; Amadio, P.; Doni, A.; Sironi, M.; Tartari, S.; Mantovani, A.; Bottazzi, B.; Garlanda, C.; Tremoli, E.; Catapano, A.; et al. (Elsevier BV, 2016)
© 2016 The Authors. Aim: The long pentraxin PTX3 plays a non-redundant role during acute myocardial infarction, atherosclerosis and in the orchestration of tissue repair and remodeling during vascular injury, clotting and fibrin deposition. The aim of this work is to investigate the molecular mechanisms underlying the protective role of PTX3 during arterial thrombosis. Methods and results: PTX3 KO mice transplanted with bone marrow from WT or PTX3 KO mice presented a significant reduction in carotid artery blood flow following FeCl 3 induced arterial thrombosis (-80.36 ± 11.5% and -95.53 ± 4.46%), while in WT mice transplanted with bone marrow from either WT or PTX3 KO mice, the reduction was less dramatic (-45.55 ± 1.37% and -53.39 ± 9.8%), thus pointing to a protective effect independent of a hematopoietic cell's derived PTX3. By using P-selectin/PTX3 double KO mice, we further excluded a role for P-selectin, a target of PTX3 released by neutrophils, in vascular protection played by PTX3. In agreement with a minor role for hematopoietic cell-derived PTX3, platelet activation (assessed by flow cytometric expression of markers of platelet activation) was similar in PTX3 KO and WT mice as were haemostatic properties. Histological analysis indicated that PTX3 localizes within the thrombus and the vessel wall, and specific experiments with the N-terminal and the C-terminal PTX3 domain showed the ability of PTX3 to selectively dampen either fibrinogen or collagen induced platelet adhesion and aggregation. Conclusion: PTX3 interacts with fibrinogen and collagen and, by dampening their pro-thrombotic effects, plays a protective role during arterial thrombosis.